The Lives of Women in Plutarch’s Lives - Juchnevičienė, Nijolė (Literatūra, 2020)
Plutarch’s works often serve as a starting point for feminist criticism – the writer is called both a feminist who surpassed his times and a spokesperson for the traditional patriarchal society who sees women as passive and inferior to men. Others are certain that Plutarch hates women and atributes all possible character flaws to them. According to some, Plutarch despises educated women, yet others, contrarily, state that he enjoyed the company of educated women no less than that of educated men. Such a vast range of different expert opinions may be due to Plutarch’s vast literary legacy as well as the peculiarity of his way of thinking and his “generic sensibility”: the tendency to change his approach in consideration of different generic demands. Nevertheless, it is impossible to disagree that Plutarch did write the lives of men, and not of women. However, in the remaining Lives of famous Greeks and Romans, we meet plenty of women whose acts and moral principles may serve as examples not only for women, but also for men. The aim of this article is to demonstrate that Plutarch, despite of sometimes relying on stereotypes, regards women according to the same ethical principles as he applies to men. Plutarch depicts women not as passive and submissive, but as autonomous and mature characters who are active not only in their private world, but in the political world too. They overstep the traditional social boundaries of the stereotype “feminine matrix.” He accentuates two of women’s social roles that, according to his judgement, are of the greatest importance: motherhood and partnership. In Plutarch’s narrative, women are associated with love – the selfless motherly love, or marital love based on the community of thoughts and feelings. Plutarch draws attention not to the physical beauty of women, which is traditionally related to feminine sexuality in masculine psychology, but to the integrity of their characters. Love between a husband and wife, based not only on eros, but on devotion and friendship, is the primary representation of erotic love in his Lives.